Accelerated Atmospheric Corrosion in a Cast Astm a48 Gray Iron [Corrosión Atmosférica Acelerada en Una Fundición Gris Astm a48 - Sipos-Hrabal, K; Monsalve-Gonzalez, A; Artigas-Abuin, A; Allende-Seco, R (Universidade Federal do Rio de Janeiro, 2018)
Due to the long times required to investigate atmospheric corrosion resistance of metals, data on the subject is scarce. One of these studies is the one made by Southwell et al., where the effect of corrosion in a cast gray iron during 16 years was studied in various environments. This research shows and discusses the behavior of cast gray iron when subject to an accelerated corrosion test, which involves wetting in a salt spray chamber, washing and drying cycles during 40 days. Furthermore, samples were submerged in sea water, both natural and UV-sterilized. A direct relationship amongst the presence of bacteria and an increase of surface roughness was found when subject to these conditions during 14 days. Results show that the cast gray iron shows a bimodal behavior, like the observations reported by Melchers on low-alloy steels and the research by Southwell.et al. As described by Melchers, this behavior generates an inflection point in the evolution of corrosion influenced by the presence of bacteria on the metal/corrosionproducts interphase. This is validated observing evidence of bacterial activity identifying the presence of sulphur on the corrosion products by EDS after the accelerated corrosion tests. As observed, accelerated corrosion testing can simulate in a short period the conditions under which marine atmospheric corrosion takes place on cast gray iron during years, including the evidence of bacterial activity. © 2018, Universidade Federal do Rio de Janeiro. All rights reserved.